Interfacial Properties of Nano-Silica Modified Cfrps under Cryogenic Condition. Issue 3 (March 2014) - Wang, Rongguo; Zhang, Chengwei; Hao, Lifeng; Jiao, Weicheng; Yang, Fan; Liu, Wenbo
The change of interface performance between carbon-fiber and matrix resin influence the properties of carbon-fiber reinforce polymer composites (CFRPs) when temperature was changed from room temperature to cryogenic conditions. In order to find the interfacial properties of epoxy/nano-silica matrix CFRPs under cryogenic conditions, the interfacial shear strength (IFSS) and the interlaminar shear strength (ILSS) were investigated at room temperatures and 77K respectively. The morphology of fractured interface was investigated by scanning electron microscope (SEM). The results show that there are higher mechanical properties of interface at 77K condition.